PENERAPAN SISTEM PEMBERATAN PIDANA RECIDIVE GUNA MEMBERANTAS NARKOTIKA - Julian Devara Asyraf; Ade Adhari (Fakultas Hukum Universitas Tarumanagara, 2021)
This research is a normative legal research by collecting data on criminal decisions on the issue of narcotics recidivist Indonesia. This study uses a legal approach and a case approach that is related to the problems in this study, which are criminal cases regarding. The purpose of punishment is as a deterrent effect, coaching and educating the perpetrators so that they do not repeat their actions again and become better individuals in carrying out their lives so as to create security and protection for the people in Indonesia from the effect of drugs abuse and Undang-Undang Narkotika Nomor 35 Tahun 2009 concerning Narcotics can be used as a policy formulation that can be used as a policy that is used as a step to provide legal certainty to the community and also as an alternative to solving problems. Moreover, it can be used as a step as a preventive to recidivism which in essence is an integral part of efforts to provide legal certainty to the public, as well as a step alternative in solving a legal issue.